JEPARA WOOD CARVING AND THE CULTURAL INFLUENCES OF THE NUSANTARA MARITIME SPICE ROUTE - Freddy Chrisswantra (Serat Rupa: Journal of Design, 2021)
The increasing need for spices in the world triggers various expeditions to find sources of spices in the world. The activity of searching for the origin of these spices gave birth to international trade systems and routes. The emergence of this spice route resulted in the emergence of trading ports which became the forerunner to the emergence of new kingdoms. Jepara was one of the kingdoms that emerged because it had a port in a strategic area on the spice trade route. The hustle and bustle of trading activities in Jepara also affects the social life of the Jepara people who have long been known for their carving skills. Traders who come from various parts of the country and abroad open up opportunities for cultural mixing, which has an impact on culture, expertise, and the application of patterns in the art of Jepara wood carving. In this paper, the researcher tries to mitigate the development and influence of acculturation brought by foreign traders with a historiography method to make it easier to read the impact of the maritime spice route on the development of carving in Jepara. The results of this study shows the application of various wood carving motifs to various artifacts as a result of the influence of the mixed culture in Jepara at that time.